Employee/Work Engagement and Organizational Performance: A Combined Bibliometric and Systematic Literature Review - Maurits Sahata Sipayung; Gordius Ago (International Journal of Marketing & Human Resource Research, 2026)
This paper examines the relationship between employee/work engagement (EE/WE) and organizational performance by combining bibliometric analysis and a systematic literature review (SLR). It aims to map the development of the literature, identify the main thematic structure of the field, and synthesize direct and supporting evidence linking EE/WE to organizational performance. Lens was used as the primary database, while Google Scholar via Publish or Perish served as a supplementary source. After deduplication and title–abstract screening, 266 records were retained for bibliometric mapping. From this corpus, 74 full-text articles were reviewed in detail and classified into 31 core studies, 26 supporting studies, and 17 non-core studies. The bibliometric results reported in this paper focus on publication trends, keyword co-occurrence and thematic evolution, and bibliographic coupling by source. The findings show that the literature has expanded markedly since 2022 and has increasingly shifted from a traditional organizational behavior orientation toward a more strategic and capability-based perspective. The systematic synthesis further indicates that EE/WE is generally associated with stronger organizational outcomes across sectors, although the evidence is stronger for non-financial and multidimensional organizational performance than for purely financial performance. The review also suggests that the engagement–performance relationship frequently operates through indirect pathways such as job satisfaction, commitment, resilience, customer-oriented behavior, and HRM-related processes. Overall, EE/WE emerges as a strategic organizational resource, while the literature still requires more longitudinal, multi-source, organization-level, and financially focused studies